Udder skin temperature is related to the ewes’ and lambs’ behaviors at birth in autumn lambing ewes - Ungerfeld, Rodolfo; Menant, Ophélie; Pérez-Clariget, Raquel; Freitas-de-Melo, Aline (Frontiers in Ethology, 2025)
The survival of lambs depends on various factors, including the behavioral traits of both mother and newborn lambs at birth, as well as the ewe’s colostrum production and quality. Colostrum consumption is essential for establishing the ewe-lamb bond and for increasing the lambs’ survival rate. The lambs’ survival rate is also related to the ewe’s udder and teat morphological characteristics. The aim of this study was to determine whether udder and teat characteristics before lambing are associated with the ewe-lamb behaviors at birth and during a separation-reunion test performed 24–36 h later. The udder’s volume and the length, width, and angle of the teats, and the udders’ skin surface temperatures were measured on ewes before lambing. At lambing, the duration of the second stage of parturition, the latency of the ewe to lick the lamb for the first time and its duration, and the latency of the lamb to suckle for the first time and the suckle duration were recorded. Twenty-four to 36 h postpartum, a separation-reunion test was performed during which the ewe’s and lamb’s vocalizations, the ewe-lamb distance, and the latency to reunite and suckle were recorded. Data were collected on 50 ewe-lamb dyads during an out-of-season lambing period (autumn). Spearman correlations were conducted between udder and teat characteristics and the behaviors of ewes and lambs after birth. The udder surface skin temperatures of the ewes’ were negatively related with the number of days before lambing (max: r=-0.57, P = 0.003, min: r= -0.50, P = 0.01), but were positively associated with the latency of the ewe to lick the lamb for the first time (min: r=0.46, P = 0.03), and the latency of the lambs to suckle for the first time (max: r=0.53, P = 0.007, min: r= 0.46, P = 0.02). In conclusion, a negative correlation was observed between the udder skin surface temperature and the time it took for the mothers to lick their lambs for the first time, as well as the time it took for the lambs to ingest colostrum for the first time. However, the morphological characteristics of the udder and teats recorded before birth were not found to be related to the behavioral development of the ewe-lamb bond.